(untitled) (gjstudies, 2017)
This research investigates the unique and often overlooked accounting governance challenges faced by nonprofit sector organizations, moving beyond traditional compliance-basedframeworks to examine systemic vulnerabilities. While existing literature predominantly focuses on for-profit corporate governance, this study adopts a novel, socio-technical systemsperspective to analyze how the interplay between mission-driven objectives, resource constraints, and stakeholder expectations creates distinct governance pathologies. We propose ahybrid methodological approach, integrating qualitative case study analysis of three diversenonprofit organizations with a quantitative analysis of Form 990 data from a stratified sampleof 150 entities, spanning the years 1995 to 2004. Our findings reveal a critical tension between’accountability for mission’ and ’accountability for resources,’ a dichotomy not adequately addressed by current standards. We identify a recurring pattern of ’informal governance adaptation,’ where organizations develop internal, non-standardized accounting practices to navigatecomplex donor restrictions and programmatic reporting needs, often at the expense of transparency and comparability. Furthermore, the research uncovers that technological adoption ofbasic accounting software, rather than mitigating these issues, can inadvertently ossify theseinformal practices by lacking the flexibility required for nonprofit-specific reporting. The studyconcludes that prevailing accounting governance models, largely imported from the for-profitsector, are ill-suited to the nonprofit context, leading to a facade of compliance that masksunderlying accountability gaps. We contribute originality by framing these challenges not asfailures of implementation but as inherent structural conflicts within the nonprofit ecosystem,suggesting the need for a fundamentally redesigned, principle-based governance frameworktailored to mission-centric accountability.